2013
DOI: 10.17221/57/2011-pps
|View full text |Cite
|
Sign up to set email alerts
|

Infection process in resistant and susceptible maize (Zea mays L.) genotypes to Cercospora zeae-maydis (type II)

Abstract: Lyimo H.J.F., Pratt R.C., Mnyuku R.S. O.W. (2013): Infection process in resistant and susceptible maize (Zea mays L.) genotypes to Cercospora zeae-maydis (type II). Plant Protect. Sci., 49: 11-18.The infection process of Cercospora zeae-maydis type II (syn. Cercospora zeina Meisel and Korsman) in resistant, moderately resistant and susceptible maize genotypes was studied in the greenhouse under artificial inoculation. The percent spore germination, germ tube growth and formation of mature appressorium on leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…We noted that both RIL387 and RIL165 had differential expression of terpenoid biosynthetic genes that provide the building blocks for phytoalexin production. Phytoalexins have been proposed to provide resistance to C. zeina infection [ 93 ], and therefore we investigated the induction of phytoalexin biosynthetic gene expression and phytoalexin accumulation in both genotypes using a glass house time course analysis of maize leaves inoculated with C. zeina . Both families of maize phytoalexins accumulated in response to C. zeina , albeit, zealexins were more abundantly elicited than kauralexins in both genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…We noted that both RIL387 and RIL165 had differential expression of terpenoid biosynthetic genes that provide the building blocks for phytoalexin production. Phytoalexins have been proposed to provide resistance to C. zeina infection [ 93 ], and therefore we investigated the induction of phytoalexin biosynthetic gene expression and phytoalexin accumulation in both genotypes using a glass house time course analysis of maize leaves inoculated with C. zeina . Both families of maize phytoalexins accumulated in response to C. zeina , albeit, zealexins were more abundantly elicited than kauralexins in both genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, reported that yield losses due to gray leaf spot on resistant, moderately resistant, and susceptible varieties were between 0-14. 9%, 13.7-18.3% and 20.8-49.5%, respectively in Bako and its surrounding areas (Lyimo et al, 2013;.…”
Section: Introductionmentioning
confidence: 91%
“…Gray leaf spot caused by Cercospora zeae maydis has become one of the major yield-limiting diseases of maize in eastern Africa including Ethiopia ( Bekeko et al, 2018). This disease is most severe and damaging when periods of high relative humidity extended, slowdrying of dews and prolonged late-season fogs (Lyimo et al, 2013). Increased incidence of gray leaf spot in Ethiopia has been associated with cultural practices such as reduced tillage, continuous cultivation of maize, and use of susceptible maize cultivars (Wegary et al, 2008;Worku et al, 2012).…”
Section: Introductionmentioning
confidence: 99%